Association of the android to gynoid fat ratio with nonalcoholic fatty liver disease: a cross-sectional study - Yang, Ling; Huang, Hangkai; Liu, Zhening; Ruan, Jiaqi; Xu, Chengfu (Frontiers in Nutrition, 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is becoming a severe global public health problem, but its risk factors have not been fully identified. This study aimed to explore the association of the android to gynoid fat ratio (A/G ratio) with the risk of NAFLD. Methods: This cross-sectional study included 4,706 participants of the National Health and Nutrition Examination Survey. Participants aged 20 and older without viral hepatitis or significant alcohol consumption were included. Dual-energy X-ray absorptiometry was used to assess body composition. NAFLD was diagnosed using the United States fatty liver index (US FLI). Multivariable logistic regression models were used to evaluate the association between the A/G ratio and NAFLD. Results: The prevalence of NAFLD was 27.77% among the study population. Android percent fat and the A/G ratio were significantly higher in patients with NAFLD than in those without NAFLD [40.95 (0.22) vs. 32.54 (0.24), P <0.001; 1.19 (0.01) vs. 0.97 (0.01), P <0.001, respectively]. Logistic regression analysis showed that android percent fat was a risk factor for NAFLD (OR: 1.17, 95% CI: 1.13–1.22), while gynoid percent fat was a protective factor (OR: 0.90, 95% CI: 0.88–0.93), and the A/G ratio was an independent risk factor for NAFLD (OR: 1.75, 95% CI: 1.47–2.08). We also found that females had a notably diminished A/G ratio compared with males (0.90 ± 0.01 vs. 1.12 ± 0.01, P <0.001). In addition, the female population proportion was negatively correlated with the A/G ratio, which may partly explain the lower prevalence of NAFLD in females. In addition, the OR value of the A/G ratio in the female subgroup was much higher than that in the male subgroup in all adjusted models. Conclusions: Android percent fat and the A/G ratio are risk factors for NAFLD, while gynoid percent fat is the opposite. Women have a lower A/G ratio than men, which may explain the sex difference in NAFLD prevalence. Moreover, females with a higher A/G ratio are at greater risk of NAFLD.